2000
DOI: 10.1128/aem.66.1.186-193.2000
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Nuclear Magnetic Resonance Studies of Xylose Metabolism by Recombinant Zymomonas mobilis ZM4(pZB5)

Abstract: The specific rates of growth, substrate utilization, and ethanol production as well as yields of biomass and ethanol production on xylose for the recombinant Zymomonas mobilis ZM4(pZB5) were shown to be much less than those on glucose or glucose-xylose mixtures. Typical fermentations with ZM4(pZB5) growing on glucosexylose mixtures followed two-phase growth kinetics with the initial uptakes of glucose and xylose being followed by slower growth and metabolic uncoupling on xylose after glucose depletion. The red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
(49 reference statements)
3
32
0
1
Order By: Relevance
“…At a metabolite level, it was observed that A3 produced much less xylitol during xylose fermentation. As previously suggested by other researchers (Feldmann et al, 1992;Jeon et al, 2005;Kim et al, 2000;Scangos and Reiner, 1979), xylitol formation and its toxicity may be an important factor. This was investigated as a potential reason for the improvement in A3.…”
Section: Reduced Xylitol Production and Increased Xylitol Tolerance Imentioning
confidence: 66%
See 3 more Smart Citations
“…At a metabolite level, it was observed that A3 produced much less xylitol during xylose fermentation. As previously suggested by other researchers (Feldmann et al, 1992;Jeon et al, 2005;Kim et al, 2000;Scangos and Reiner, 1979), xylitol formation and its toxicity may be an important factor. This was investigated as a potential reason for the improvement in A3.…”
Section: Reduced Xylitol Production and Increased Xylitol Tolerance Imentioning
confidence: 66%
“…Thus, xylose fermentation at high concentration is a better measure for a strain's ability to use xylose than mixed sugar fermentation. Previously, the highest xylose concentration that supports cell growth was $6% (Kim et al, 2000;, and in some cases, the fermentation was incomplete with significant amount of residual xylose (>1%; .…”
Section: Drastic Improvement In Xylose Fermentation By Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal itu menyebabkan penambahan kadar gula reduksi ke dalam media fermentasi. Menurut Kim et al (2000) Z. mobilis cenderung akan mengkonsumsi monosakarida terlebih dahulu ketika tumbuh dalam media campuran antara monosakarida dan disakarida.…”
Section: Kadar Gula Reduksiunclassified